Enhancing photovoltaic performance via aggregation dynamics control in fused‐ring electron acceptor. Issue 3 (2nd February 2021) - Wang, Jiayu; Zhu, Runyu; Wang, Shijie; Li, Yawen; Jia, Boyu; Zhou, Jiadong; Xue, Peiyao; Seibt, Susanne; Lin, Yuze; Xie, Zengqi; Ma, Wei; Zhan, Xiaowei
Abstract: A new fused‐ring electron acceptor FNIC3 with dynamics controlled aggregation behavior was synthesized. FNIC3 shows strong absorption in 600–900 nm, HOMO/LUMO energy levels of −5.59/−4.04 eV, and electron mobility of 1.2 × 10 −3 cm 2 V −1 s −1 . The aggregation of FNIC3 shows strong dependency on film formation time. Prolongation of film formation time promotes the crystallization of FNIC3, leading to improved crystallinity and enlarged aggregate sizes. Aggregation of FNIC3 significantly influences the photovoltaic device parameters. Appropriate aggregation red‐shifts the absorption and improves the mobilities of the blend, which contributes to high photocurrent and fill factor thus high power conversion efficiency (PCE). Overaggregation leads to increased nonradiative energy loss and insufficient charge generation, resulting in decreased open‐circuit voltage and short‐circuit current density. The blends based on PM6:FNIC3 fabricated under proper film formation time exhibit a PCE of 12.3%, higher than those fabricated under short and long film formation time (10.0–10.5%). Abstract : A new fused‐ring electron acceptor FNIC3 with dynamics controlled aggregation behavior is synthesized. The aggregation states of FNIC3 and thus the optical, electronic and morphological properties of active layer are tuned by altering film formation time. A power conversion efficiency of 12.3% is achieved under appropriate aggregation states, over 20% enhancement relative to the control devices (10.0%).